2016
DOI: 10.1063/1.4943267
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory based study of chlorine doped WS2-metal interface

Abstract: Investigation of a TMD-metal interface is essential for the effective functioning of monolayer TMD based field effect transistors (FETs). In this work, we employ Density Functional Theory (DFT) calculations to analyze the modulation of the electronic structure of monolayer WS 2 with chlorine doping and the relative changes in the contact properties when interfaced with gold and palladium. We initially examine the atomic and electronic structures of pure and doped monolayer WS 2 supercell and explore the format… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Their studies demonstrated that WS 2 monolayers doped by Ni, Pd, and Pt are ferromagnetic and suitable for thin dilute magnetic semiconductors. Chanana et al [ 12 ] studied the chlorine-doped WS 2 -metal interface and found that WS 2 physiosorbed with Au has an n-type Schottky barrier height (SBH) while the one chemisorbed with Pd has a p-type SBH. The electronic and optical properties of a vacancy-doped WS 2 monolayer has been studied by Wei et al [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their studies demonstrated that WS 2 monolayers doped by Ni, Pd, and Pt are ferromagnetic and suitable for thin dilute magnetic semiconductors. Chanana et al [ 12 ] studied the chlorine-doped WS 2 -metal interface and found that WS 2 physiosorbed with Au has an n-type Schottky barrier height (SBH) while the one chemisorbed with Pd has a p-type SBH. The electronic and optical properties of a vacancy-doped WS 2 monolayer has been studied by Wei et al [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…To understand the interfacial interaction, the charge differential density, defined in the off-interfacial direction by Dr = r PtSe 2 -M À r PtSe 2 À r M , on PtSe 2 -2D metal contacts was analyzed. 69,[82][83][84] Here, r PtSe 2 -M , r PtSe 2 , and r M denote the plane-averaged charge density of the PtSe 2 -2D metal contacts, freestanding isolated PtSe 2 , and freestanding isolated 2D metals, respectively. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[ 209 ] The impurity of Cl was calculated to reduce the n‐type Schottky barrier in the WS 2 and metal contacts. [ 210 ]…”
Section: Properties and Applications Of Halogenated 2d Materialsmentioning
confidence: 99%